OBTAINING OF HIGH-PERFORMANCE LUMINOPHOR AND SEVERAL NEW TYPES OF WATERPROOFING MATERIALS THROUGH INNOVATIVE TECHNOLOGY (World Science, 2021)
The Baku-Tbilisi-Ceyhan oil pipeline runs through the territory of Georgia.During the operation of the said oil pipeline some sludge with a heavy, viscous mass is formed on its walls, which must be removed with defined regularity. The interest of our research in particular is this product - the residual mass of the pipeline, the so-called "wax". It should be noted that the amount of this residue increases annually, and its non-use causes pollution of the environment, the loss of cheap raw materials and the possibility of obtaining scarce low-tonnage products from it. The main purpose of the work is to study the remainder of the pipeline ("wax") as a raw material for obtaining of commodity products.